QUALITE DES POISSONS VENDUS AU PORT DE PECHE ARTISANAL DE COTONOU (POPAC) - Charles Lambert Babadjide; Bernard Fangnon; Sidonie Clarisse Hedible (European Scientific Journal, ESJ, 2015)
The cleanliness of the environment we live in is one of the major concerns of environmental management, and human actions should contribute to all men and women’s well-being. The aim of this study is to analyse the influence of the fishing communities’ behaviour on the quality of the fish at the traditional Fishing Harbour in Cotonou. The methodology used has made it possible to use the statistics available on the fish, the fishermen and the wholesale fishmongers, to do literature review, to conduct interviews, to watch, to ask questions and to develop tools with a sample of fishermen and wholesale fishmongers. The data collected so far have been processed and analysed. Given the results achieved, it is possible to say that the fishing community of the traditional Fishing Harbour in Cotonou is made up of many stakeholders. Most consumers of fishing products go to the Fishing Harbour in Cotonou to buy these products. Before the fish leaves the fishermen’s row-boats and gets to the consumers, its quality deteriorates. The fishing community contributes to polluting the fish sold at the harbour. The various tests carried out (on the area, the fish, the water and the ice) in IRGIB-Africa’s laboratory in 2012 revealed the presence of total coliform counts, fecal coliforms, staphylococcus and anaerobics and some sulfite. The tests indicate that 70% of the fish contain disease-causing flora, 80% contain fecal coliforms, 70% contain staphylococcus and 70% contain anaerobic germs and a level of sulfite which is higher than the required standards. These elements show that the fish sold at the Fishing Harbour in Cotonou is polluted.